2008
DOI: 10.1159/000116740
|View full text |Cite
|
Sign up to set email alerts
|

Feticide Does Not Modify Duration of Labor Induction in Cases of Medical Termination of Pregnancy

Abstract: Objectives: To compare the general characteristics and clinical outcome of women who underwent medical termination of pregnancy preceded or not by feticide. Methods: A total of 146 women of diverse gestational ages, who had received a sonographic or genetic diagnosis of fetal abnormality incompatible with postnatal life and chose to legally terminate their pregnancy, had labor induced following feticide (n = 82) or without having feticide performed (n = 64). Results: The number of obstetrical procedures was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Silva et al [19] reported that CNS abnor- malities (60%) were the most common indication as comparable with our results. However, the proportion of CNS abnormalities was relatively lower in our population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Silva et al [19] reported that CNS abnor- malities (60%) were the most common indication as comparable with our results. However, the proportion of CNS abnormalities was relatively lower in our population.…”
Section: Discussionsupporting
confidence: 93%
“…However, some previous data do not support these results. Although Silva et al [19] found shorter I-to-A interval in the feticide group compared with that of the non-feticide group (mean duration of 42.9 vs. 53.2 h), the difference was not statistically significant. Heterogeneity in medical treatment may have led to a conservative bias in their study and precluded the real effect of the feticide.…”
Section: Discussionmentioning
confidence: 72%
“…In one study, the effect of feticide on the duration of labour induction was examined retrospectively and there was no significant difference noticed in the outcome except that the group with feticide tend to have more procedure in the form of manual extraction of placenta or uterine curettage or both (82.9 versus 65.6%, P = 0.01) [22]. This study differs from the other studies above in that it is not stratified according to the method of termination but rather whether feticide was performed or not.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference between the two groups in terms of complications at the 12 th , 24 th , and 48 th hours21. In one study, the effect of feticide on the duration of labor induction was examined retrospectively and there was no significant difference noticed in the outcome except that the group with feticide tended to have more procedures in the form of manual extraction of placenta or uterine curettage or both (82.9 vs. 65.6%, P = 0.01)22. The results also showed that performing feticide procedures had no effect on the termination duration.…”
Section: Discussionmentioning
confidence: 99%